Usefulness of Parasternal Intercostal Muscle Ultrasound during Weaning from Mechanical Ventilation. (May 2020) - Dres, Martin; Dubé, Bruno-Pierre; Goligher, Ewan; Vorona, Stefannie; Demiri, Suela; Morawiec, Elise; Mayaux, Julien; Brochard, Laurent; Similowski, Thomas; Demoule, Alexandre
Abstract : Background: The assessment of diaphragm function with diaphragm ultrasound seems to bring important clinical information to describe diaphragm work and weakness. When the diaphragm is weak, extradiaphragmatic muscles may play an important role, but whether ultrasound can also assess their activity and function is unknown. This study aimed to (1) evaluate the feasibility of measuring the thickening of the parasternal intercostal and investigate the responsiveness of this muscle to assisted ventilation; and (2) evaluate whether a combined evaluation of the parasternal and the diaphragm could predict failure of a spontaneous breathing trial. Methods: First, an exploratory evaluation of the parasternal in 23 healthy subjects. Second, the responsiveness of parasternal to several pressure support levels were studied in 16 patients. Last, parasternal activity was compared in presence or absence of diaphragm dysfunction (assessed by magnetic stimulation of the phrenic nerves and ultrasound) and in case of success/failure of a spontaneous breathing trial in 54 patients. Results: The parasternal was easily accessible in all patients. The interobserver reproducibility was good (intraclass correlation coefficient, 0.77 (95% CI, 0.53 to 0.89). There was a progressive decrease in parasternal muscle thickening fraction with increasing levels of pressure support (Spearman ρ = −0.61 [95% CI, −0.74 to −0.44]; P < 0.0001) and an inverse correlation between parasternal muscle thickening fraction and the pressure generating capacity of the diaphragm (Spearman ρ = −0.79 [95% CI, −0.87 to −0.66]; P < 0.0001). The parasternal muscle thickening fraction was higher in patients with diaphragm dysfunction: 17% (10 to 25) versus 5% (3 to 8), P < 0.0001. The pressure generating capacity of the diaphragm, the diaphragm thickening fraction and the parasternal thickening fraction similarly predicted failure or the spontaneous breathing trial. Conclusions: Ultrasound assessment of the parasternal intercostal muscle is feasible in the intensive care unit and provides novel information regarding the respiratory capacity load balance. Abstract : Parasternal intercostal muscle thickness can be measured with ultrasound with good interobserver reproducibility. Parasternal intercostal muscle thickening was responsive to the level of ventilator assistance and significantly higher ( i.e., increased) in mechanically ventilated patients with diaphragm dysfunction. The pressure generating capacity of the diaphragm, the diaphragm thickening fraction, and the parasternal intercostal muscle thickening fraction were all significantly associated with failure of a spontaneous breathing trial in mechanically ventilated patients.Supplemental Digital Content is available in the text.